THE USE OF EGGSHELL WASTE AS A MEDIA OF VEGETABLE BREEDING AT CULINARY DEPARTMENT OF SMK NEGERI 4 YOGYAKARTA - Purwanti, Heni; Heruwati, Yuni (Universitas Ahmad Dahlan, 2020)
School is a part of the environment where the learning process takes place, in addition to that the school environment is also a place of education. The learning process is expected to be a habit of self, and from the habituation of the self becomes an attitude or character and further develops as a culture. Thus the school environment can be used as a barometer in forming habits called attitudes or characters. In a school environment where residents are educated and educated people it should be easier to shape the character and culture of the school's inhabitants. The development of these characters with the hope of course towards a good or positive.Related to the culture of managing waste at Adiwiyata School, in the culinary department of SMK Negeri 4 Yogyakarta, a school which is a very strategic environment as a place of learning and education for students in order to foster a sense of love for the environment, one of which is by utilizing the organic waste that is produced by many departments namely chicken eggshell waste. Chicken eggs are one of the foods that are widely used to process food in the culinary majors of SMK Negeri 4 Yogyakarta. Various types of processed foods use chicken eggs as the main ingredient or as supporting material or additives in processed foods. The need for chicken eggs is quite large every day, causing an abundance of chicken eggshell waste in the culinary majors of SMK Negeri 4 Yogyakarta.The practice of utilizing chicken eggshell waste as a vegetable nursery media by culinary students who initially only aimed at reducing the amount of trash in the school environment turned out to get other benefits, namely egg shells can also fertilize vegetable crops.